The relationship between pelvic organ prolapse and short birth intervals in a rural area of Nepal - Rupa Singh; Sandeep Mahat; Sonam Singh; Carolyn K. Nyamasege; Yukiko Wagatsuma (Tropical Medicine and Health, 2021)
Abstract Background Pelvic organ prolapse (POP) is one of the main contributors to reproductive health problems that affect women’s quality of life. Previous studies have reported the risk factors and prevalence of POP. The aim of this study is to examine the association between POP and short birth intervals in a rural area of Nepal. Methods A cross-sectional study was conducted in Panchapuri municipality, located in Surkhet District of Karnali Province in Nepal. A questionnaire was used to collect information on POP, birth intervals, and other known confounding factors, such as age and parity. Multiple logistic regression analysis was used to examine the association between minimum birth intervals and POP. Results The study recruited 131 women. The prevalence of POP was 29.8%. The mean (SD) of maternal age was 32.3 (0.7) years. The median parity was 2, with a range of 2–6 children. More than half (64.9%) of the women reported a minimum birth interval of less than 2 years. Maternal age at birth, minimum birth interval, parity, and latest birth interval were significantly associated with POP in univariate analyses. After adjusting for the potential confounding factors such as age and occupation, the minimum birth interval was significantly associated with POP [AOR = 3.08, 95% CI 1.04–9.19]. Conclusion The prevalence of POP was high in this rural area of Nepal. Age, parity, occupation, and minimum birth interval were significantly associated with POP.